Voltage stability based contingency ranking for power system analysis / Hasnita Ramli - Ramli, Hasnita (2000)
This project report presents a method for identification of system instability and contingency ranking analysis. Voltage collapse may occur in a power system due to lost in voltage stability in the system. Therefore voltage stability analysis is important in order to identify critical buses in a power system i.e which are closed to their voltage stability limit. The objective of contingency ranking is to shortlist a specified number of critical contingencies from a large list of credible contingencies and rank them according to their severity. This project paper describes the Newton Raphson load flow method and voltage stability index for voltage stability indication with respect to a load bus. The voltage stability index then used to rank the contingencies of the system.